Correlates of physical, psychological, and social frailty among formerly incarcerated, homeless women. Issue 7 (20th August 2019) - Salem, Benissa E.; Brecht, Mary-Lynn; Ekstrand, Maria L.; Faucette, Mark; Nyamathi, Adeline M.
Abstract: Frailty is a deficit accumulation in physical, psychological and social domains. Correlates of frailty were explored among formerly incarcerated, homeless women ( N = 130, M age = 38.9). Significant correlates of physical frailty were age, years homeless, prior violence, witnessing less violence, drug dependence, PTSD symptoms and tangible support. Significant correlates of psychological frailty were age, years homeless, witnessed violence, jail time, divorced less, drug use/dependence, prison time, methamphetamine use, and bodily pain. Significant correlates of social frailty were drug use, emotional regulation, and daily alcohol use. Reentry interventions are needed for formerly incarcerated, homeless women who experience physical, psychological and social frailty.